Evaluation of fatty acid and antioxidant variation in a complex pasture system as compared to standard cattle feed in the Great Lakes region - Krusinski, Lucas; Maciel, Isabella C. de Faria; Sergin, Selin; Goeden, Travis; Ali, Humza; Kesamneni, Srikar; Jambunathan, Vijayashree; Cassida, Kimberly A.; Singh, Sukhdeep; Medina-Meza, Ilce G.; Rowntree, Jason E.; Fenton, Jenifer I. (Frontiers in Sustainable Food Systems, 2022)
As the demand for grass-fed ruminant products keeps increasing, more data is needed to assess the nutritional value of feedstuffs, especially pastures. In addition, global climate change adds another challenge to the management of grasslands with projections of changing temperature and precipitation patterns. Consequently, the variations in bioactive compounds such as fatty acids and antioxidants in feeds will be harder to predict. Therefore, it is critical to report region and time-specific results of the nutritional value of feeds intended for ruminant nutrition. The objectives of this study were to compare the antioxidant and fatty acid content of commonly used feedstuffs including a complex pasture mixture from the Great Lakes Region and a traditional grain-based diet, and to assess the variations of these bioactive compounds in the pasture over the course of two grazing seasons. Weather parameters including temperature and rainfall were recorded for the length of the study. Feed samples were collected between June and September 2019 and 2020 and analyzed for nutrient composition, chlorophyll A and B, carotenoids, and total phenols. Fatty acids were analyzed by GC-MS. Correlations were reported to analyze the relationship between individual plant species, antioxidants, and fatty acids. We observed higher antioxidant parameters in the pasture compared to the grain diet. Total polyunsaturated fatty acids were higher in the pasture including alpha-linolenic acid while the grain diet was higher in n-6 polyunsaturated fatty acids including linoleic acid. The n-6:n-3 ratio was more beneficial in the pasture and was 50 to 90 times higher in the grain diet. Variations in the fatty acid profile of the pasture were observed and varied between 2019 and 2020. Plant growth cycles, climatic conditions, and grazing methods were hypothesized to cause these changes. Altogether, this study increased our knowledge about the nutritional value of feedstuffs and will help ranchers and researchers to better understand the variations of bioactive content based on region, season, and climatic conditions. We are hopeful that this study will contribute to making more nutritious feeds and grass-fed products for human health.